2016
DOI: 10.1371/journal.pone.0154423
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analyses of Sorghum Varieties Reveal Differential Responses to Drought

Abstract: We have examined the biochemical responses of two sorghum cultivars of differing drought tolerance, Samsorg 17 (more drought tolerant) and Samsorg 40 (less drought tolerant), to sustained drought. Plants were exposed to different degrees of drought and then maintained at that level for five days. Responses were examined in terms of metabolic changes and the expression of drought induced proteins—Heat Shock Proteins (HSPs) and dehydrins (DHNs). Generalised phenotypic changes were studied using Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 56 publications
(102 reference statements)
3
23
0
Order By: Relevance
“…Studies have shown that drought-stress induce a series of physiological and morphological changes in plants, for example: growth inhibition and reduction in crop yields (Elagib 2014), enhancement of root systems and root-shoot ratios (Lu et al 2014), regulation of the closure of stomata (Wan et al 2009), disruption of photosynthesis (Zivcak et al 2013), activation of respiration (Sperlich et al 2016), accumulating compatible solutes and protective proteins (Ogbaga et al 2016;Sperdouli and Moustakas 2012), and the strengthening of anti-oxygenic enzyme activity (Bhaskara et al 2015;Hu et al 2015). These changes are controlled by gene expression, which is particularly affected by biotic and abiotic factors in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that drought-stress induce a series of physiological and morphological changes in plants, for example: growth inhibition and reduction in crop yields (Elagib 2014), enhancement of root systems and root-shoot ratios (Lu et al 2014), regulation of the closure of stomata (Wan et al 2009), disruption of photosynthesis (Zivcak et al 2013), activation of respiration (Sperlich et al 2016), accumulating compatible solutes and protective proteins (Ogbaga et al 2016;Sperdouli and Moustakas 2012), and the strengthening of anti-oxygenic enzyme activity (Bhaskara et al 2015;Hu et al 2015). These changes are controlled by gene expression, which is particularly affected by biotic and abiotic factors in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, plants developed a myriad of mechanisms to adapt or survive when exposed to drought stress, which could involve a series of molecular, biochemical, physiological, and morphological changes underlying the response of plants to water deprivation[ 13 ]. These strategies include reductions in growth rates and crop yields[ 14 ], enhancing root systems and root-shoot ratios to imbibe moisture[ 15 ], regulating the closure of stomata[ 16 ], disrupting photosynthetic pigments[ 17 ], activating respiration[ 18 ], accumulating compatible solutes and protective proteins[ 19 , 20 ], and increasing the level of antioxidants[ 21 , 22 ]. At the molecular level, the aforementioned changes will activate a range of responses, and most notably in drought-related genes that induce or inhibit gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…With recent integrated applications of MS approaches, metabolomics has emerged as a more versatile strategy than genomics and proteomics. Indeed, metabolic profiling of various crops, such as wheat, rice, maize, sorghum, and soybean, showed remarkable applications of metabolomics in plant biology [4,[41][42][43][44].…”
Section: Advanced Tools For Analytical Research In Plant Metabolomicsmentioning
confidence: 99%